Faktor – Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi Dan Bangunan Di Kecamatan Wirosari Kabupaten Grobogan - Diki Putiarawati; Maryono Maryono (Universitas Veteran Bangun Nusantara, 2023)
ABSTRACTThis study aims to examine the effect of taxpayer awareness, tax sanctions and tax knowledge on taxpayer compliance in paying land and building taxes. This research was conducted in Wirosari District, Grobogan Regency. The population in this study are all taxpayers who are subject to land and building taxes in Wirosari District, Grobogan Regency. The sampling method in this study was by using the slovin formula and using a random sampling technique with a total of 100 respondents distributed questionnaires. Testing the hypothesis in this research uses multiple linear regression analysis method. The results of the analysis in this study show that the variable of taxpayer awareness has a positive effect on taxpayercompliance, knowledge of taxation has a positive effect on taxpayer compliance. Meanwhile, the tax sanction variable has no effect on taxpayer compliance in paying land and building taxes.Keywords: Taxpayer Awareness, Tax Sanctions and Tax Knowledge